Detection of African swine fever virus in cell culture and wild boar tissues using a commercially available monoclonal antibody - Szeredi, Levente; Bakcsa, Erika; Zádori, Zoltán; Mészáros, István; Olasz, Ferenc; Bálint, Ádám; Locsmándi, Gabriella; Erdélyi, Károly (Journal of virological methods, 2020)
•A sensitive immunocytochemical (IC) and immunohistochemical (IHC) method has been developed for detection of African swine fever (ASF) virus.•The IC test has the same sensitivity as the indirect fluorescent antibody test method using polyclonal antibodies.•The IHC method detects ASF virus in all tissue samples examined from wild boar cases of acute ASF disease.•ASF virus can be detected with the IHC method in tissue samples showing advanced autolytic changes. Following the introduction of African swine fever virus (ASFV) into Europe in 2007, ASFV infection has spread continuously over the past years and it became a high level disease threat in Europe and also Asia. Examination of suspect clinical cases for ASF with rapid and sensitive laboratory methods can substantially contribute to the detection and characterization of new outbreaks. In this study two sensitive tests were developed for the detection of the p72 major capsid protein of ASFV both in cell culture with an immunocytochemical (IC) and in tissue samples with an immunohistochemical (IHC) method using a commercially available mouse monoclonal antibody (clone 1BC11). The IC test was able to detect the virus at high virus dilutions in cell culture and the IHC test indicated the presence of ASFV in all formalin-fixed and paraffin-embedded tissue samples collected from two wild boars. The reported IC and IHC methods were found to be useful ancillary laboratory tests for research purposes and for the diagnosis of acute ASF.